Circulating mortalin in blood and activation of the alternative complement pathway as risk indicators in COVID-19 infection - Avraham, Maya; Sinkovits, György; Hurler, Lisa; Prohászka, Zoltán; Fishelson, Zvi (Frontiers in Immunology, 2024)
Mortalin/GRP75 is a ubiquitous mitochondrial chaperone related to the cytosolic heat shock protein 70. It protects cells from various types of damages and from senescence. Our goal was to determine whether COVID-19 patients have circulating mortalin in their blood and to assess its prognostic value in anticipating disease severity. Mortalin was determined by ELISA in the sera of 83 COVID-19 patients enrolled in the study. Patients were categorized into 4 groups: critical patients who died (FATAL) or required intensive care and survived (ICU), patients of mild severity (hospitalized but not critical) who required nasal oxygen support (HOSP+O2), and patients who did not need oxygen therapy (HOSP). The mortalin concentration in the serum of all COVID-19 patients in the cohort was 194-2324 pg/mL. A comparison of the mortalin levels by peak severity among the various patient groups showed a highly significant difference between the HOSP and FATAL groups and a significant difference between the HOSP and the ICU groups. COVID-19 patients who eventually failed to survive had at hospitalization a markedly higher level of mortalin in their sera. Cox regression analysis revealed a high mortality hazard (HR=3.96, p<0.01) in patients with high mortalin circulating levels (above the median, ≥651 pg/mL). This was confirmed in survival curve analysis (Kaplan-Meier; p=0.0032, log-rank test). Mortalin remained an independent predictor of mortality even after adjusting for age and sex or various complement activation products. Complement activation data collected in an earlier study in the same cohort was compared regarding the mortalin levels. Patients with higher circulating mortalin levels also had higher levels of complement C3a but reduced levels of properdin. This is the first report on circulating mortalin in COVID-19 patients. Higher mortalin levels were associated with more severe illnesses and a higher risk of death. We claim that quantifying the blood levels of mortalin and activated complement proteins will provide important information on the prognosis of COVID-19 patients and will serve as a useful tool for guiding their clinical management and treatment.